BODY DIFFICULTIES IN RHYTHMIC GYMNASTICS ROUTINES - Amanda Batista; Rui Garganta; Lurdes Ávila-Carvalho (Science of Gymnastics Journal)
The aims of this study were: (1) to analyze the diversity and variety of body difficulty elements in individual routines of elite rhythmic gymnasts that competed at the 2013 and 2014 Lisbon World Cup; (2) to compare these characteristics across different ranking groups; (3) to identify and hierarchize the variables that most contribute to the success in the difficulty score in competition. 288 routines were analyzed based on difficulty, according to the 2013-2016 Code of Points. The gymnasts were divided into three groups according to their ranking routine. For statistical analyses, Kruskal-Wallis’ and Mann-Whitney’s non-parametric tests, Pearson Correlation and multiple regression were used. Among all body difficulties, the rotation elements were the group with the most variety, while jump elements had the least variety. Gymnasts tend to use the same jumps, balance elements and rotations in all their routines. The gymnasts in the finals (finalists) presented a higher number of complex elements (mixed and multiple difficulties) than the other groups. However, the best gymnasts showed a lower variety in the choice of body difficulties. Their routines focused on rotation elements and number of turns. Lower occurrences of balance and jump elements were verified. We identified the following hierarchy of importance of the variables that contribute to the success in the difficulty score: value of rotations; value of jumps; value of balance elements and value of mixed difficulties. Therefore, the rotation elements presented a higher importance in the routines in RG in the Olympic cycle 2013-2016.